Choosing crown material to avert metallic artefact in MRI scans: A case report - Leoney, Antony; Sahima, Maryam A; Indhumathi, Dharmalingam; Vallabhaneni, Saketha (International Journal of Dental Materials, 2025)
Magnetic resonance imaging creates metallic artefacts. An artefact may be defined as a distortion of signal intensity that does not have any anatomic basis in the plane being imaged. The main concerns that may arise during the MRI of a patient with a dental prosthesis include artefact creation, heat production, and/or risk of displacement. Dental materials can be classified based on their magnetic permeability properties as Diamagnetic, Paramagnetic and Ferromagnetic. This article will throw a light on choosing an appropriate material for the anterior crown, which will have the least magnetic susceptibility on MRI scans.